Development of Assessment-Oriented E-LKPD Media for Learning to Train Mathematical Problem-Solving Skills - Dadan Ramdani; Vepi Apiati; Depi Ardian Nugraha (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Students limited mathematical problem-solving ability is often related to the lack of learning media that can provide continuous feedback throughout the thinking process. This study addresses that gap by developing an electronic student worksheet (E-LKPD) based on Assessment for Learning (AfL) for one-variable linear inequalities. The novelty of this study lies in integrating AfL principles with an automated feedback system that supports reflection, enables students to identify errors, and helps them overcome difficulties independently. This feature distinguishes the product from conventional E-LKPDs, which generally do not provide structured and continuous feedback. The study used a research and development approach with the PPE model, consisting of Planning, Production, and Evaluation. Planning involved needs and curriculum analysis, Production covered storyboard design and product development using wizer.me, and Evaluation included expert validation and field trials. The participants in the implementation stage were 30 eighth-grade students of SMPN 4 Tasikmalaya. The instruments included validation questionnaires, student response questionnaires to assess practicality, and a test of mathematical problem-solving ability to measure effectiveness. Data were analyzed quantitatively and qualitatively using Aiken’s V, percentages, mean scores, N-gain, and Cohen’s d. The results showed that the developed E-LKPD was valid, with Aiken’s V scores of 0.91 from media experts and 0.92 from material experts. The media was also effective in improving students’ mathematical problem-solving ability, as indicated by a medium N-gain of 0.35 and a large effect size of 3.63. These findings indicate that AfL-based E-LKPD is feasible, practical, and effective for supporting mathematics learning in digital environments.